2006
DOI: 10.1038/nn1801
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids reveal importance of spike timing coordination in hippocampal function

Abstract: Cannabinoids impair hippocampus-dependent memory in both humans and animals, but the network mechanisms responsible for this effect are unknown. Here we show that the cannabinoids Delta(9)-tetrahydrocannabinol and CP55940 decreased the power of theta, gamma and ripple oscillations in the hippocampus of head-restrained and freely moving rats. These effects were blocked by a CB1 antagonist. The decrease in theta power correlated with memory impairment in a hippocampus-dependent task. By simultaneously recording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
289
5
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(332 citation statements)
references
References 49 publications
34
289
5
4
Order By: Relevance
“…Acute cannabinoid exposure attenuates the power of neural oscillations recorded in vitro (Hajós et al, 2000(Hajós et al, , 2008 and in vivo, in freely moving animals (Robbe et al, 2006;Hajós et al, 2008;Kucewicz et al, 2011) and during working memory tasks (Kucewicz et al, 2011) by CB1R-mediated suppression of glutamate release from pyramidal neurons (Holderith et al, 2011;Sales-Carbonell et al, 2013). This CB1R-mediated attenuation of excitatory transmission preferentially suppresses the frequency and firing precision of fast-spiking GABAergic interneurons, resulting in smaller and less synchronized field potentials (Holderith et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute cannabinoid exposure attenuates the power of neural oscillations recorded in vitro (Hajós et al, 2000(Hajós et al, , 2008 and in vivo, in freely moving animals (Robbe et al, 2006;Hajós et al, 2008;Kucewicz et al, 2011) and during working memory tasks (Kucewicz et al, 2011) by CB1R-mediated suppression of glutamate release from pyramidal neurons (Holderith et al, 2011;Sales-Carbonell et al, 2013). This CB1R-mediated attenuation of excitatory transmission preferentially suppresses the frequency and firing precision of fast-spiking GABAergic interneurons, resulting in smaller and less synchronized field potentials (Holderith et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Acute cannabinoid administration attenuates the power of oscillations (Hajós et al, 2000(Hajós et al, , 2008Robbe et al, 2006;Kucewicz et al, 2011) by acting at CB1Rs to suppress glutamate release from pyramidal neurons (Holderith et al, 2011;Sales-Carbonell et al, 2013). Furthermore, oscillations are suppressed in chronic marijuana users, particularly in those with an earlier age of onset of use (Skosnik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hampson and Deadwyler (2000) found that D 9 -THC and WIN 55,212-2 act selectively to disrupt the encoding of events in the hippocampus during memory processing, on measuring the combined simultaneous multineuron firing rate. Recently, it was also suggested that the cannabinoids D 9 -THC and a cannabinoid CB 1 receptor agonist CP55940 disrupted the temporal coordination of hippocampal neurons, and that this effect may correlate with memory deficits in individuals (Robbe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The animals performed the task for 3 days without any manipulation between test days with microinjections. The dose we used falls within the dose range of previous studies employing intracerebral application of high-affinity cannabinoid agonists including ACEA and CP55940 (Fogaca et al 2012;Miller et al 1998;Moreira et al 2007;Robbe et al 2006). All microinjections were administered in a volume of 0.5 μl per side over 60 s using a stainless steel needle (30 gauge) which was directly inserted into the guide cannula, protruding 1 mm beyond the tip of the cannula.…”
Section: Microinjections and Behavioral Testingmentioning
confidence: 99%